The Economic Role of Tourism and the Dimension of the Touristic Phenomenon on a National and Global Scale - Isac, Florin; Cureteanu, Radu; Rusu, Sergiu (Studies and Scientific Researches. Economics Edition, 2010)
Nowadays tourism represents a quite distinct field of human activity, a component of highest importance of the economic and social life for an ever larger number of countries on the globe. Tourism evolves constantly due to the changes occurring in contemporary civilization, its dynamics integrating in the general process of development.